Hierarchically porous MOF/polymer composites via interfacial nanoassembly and emulsion polymerization. Issue 41 (15th October 2018) - Jin, Peng; Tan, Wenlong; Huo, Jia; Liu, Tingting; Liang, Yu; Wang, Shuangyin; Bradshaw, Darren
Abstract : In this work, we develop a general strategy for the preparation of robust hierarchically porous and readily processable MOF composites through an interfacial nanoassembly/emulsion polymerization method. Abstract : In this work, we develop a general strategy for the preparation of robust hierarchically porous and readily processable MOF composites through an interfacial nanoassembly/emulsion polymerization method. MOF nanoparticles of different composition and stability including ZIF-8, UiO-66 and Cr-MIL-101 and moisture-sensitive HKUST-1 have been successfully incorporated into the composites. The size of macropores within the ZIF-8/polystyrene (ZIF-8/PS) composites can be controlled from 6 μm to 28.5 μm through changing the amount of MOF nanoparticles, which simultaneously tunes the loading of MOFs within the composites. The fluidic nature of the emulsion before polymerization facilitates the processibility of the MOF-composites into task-specific shapes, including columns, spheres, and various irregular bodies. Additionally, the magnetic functionality can be endowed to the MOF composites through co-assembly of Fe3 O4 and MOF nanoparticles. The MOF composites exhibit excellent mechanical stability even after pressing or long-term mechanical stirring, and the ZIF-8/PS polyHIPE shows high conversion rate toward the Knoevenagel reaction compared with bulk ZIF-8 nano- and microparticles.